DENTITION IN PATIENTS BEFORE AND AFTER ORTHODONTIC TREATMENT OF MALOCCLUSION CLASS III - MA A Postnikov; GV V Stepanov; LG G Uljanova (Наука и инновации в медицине, 2016)
Many scientists were engaged in the study of dentition anthropometry in patients before and after orthodontic treatment. The most common orthodontic device for the treatment of malocclusion class III is a regulator of Frenkel type III. We have proposed a new orthodontic device for the treatment of patients with malocclusion class III and premature removal of temporary molars. Aim - to compare changes of dentitions in children aged 6-12 before and after orthodontic treatment of malocclusion class III using the device of own design and regulator of Frenkel type III. Materials and methods. 110 patients at the age of 6-12 years with malocclusion class III were treated with the use of removable orthodontic curative devices. Anthropometry of dentitions was conducted before and after the treatment. Results. After applying the new diagnostic and treatment algorithm, the duration of orthodontic treatment of patients with malocclusion class III reduced by 1.3 times. The children's quality of life have improved after orthodontic treatment. Conclusion. In case of children aged 6-12 years with malocclusion class III associated with premature removal of temporary molars, it is necessary to use the device of our design. This will give the opportunity not only to fix the dento-facial abnormality, but also to restore the functions of chewing, swallowing and speech.